Investigation of Characteristics and Thermal Behaviour of Lignocellulosic Waste Biomass Using Thermogravimetric Analysis - Zorica Lopičić; Tatjana Šoštarić; Ahmad Hosseini-Bandegharaei; Jelena Milojković; Marija Petrović; Katarina Pantović Spajić; Jelena Avdalović (Journal of Engineering & Processing Management, 2019)
This paper focuses on lignocellulosic waste biomass originating from food industry, which should find its further application in order to fulfill demands of circular economy. Therefore, here are presented some of the chemical and physical properties that affect combustion process, as well as thermochemical reaction kinetics for lignocellulosic biomass wastes. The biomass investigated was peach stone particles originating from food industry. The results have showed that peach stones can be characterized as good energy alternative renewable material, with properties that allow its safe thermochemical conversion. Kinetic analysis of this biomass was performed using Thermogravimetric Analysis (TGA) with a simple reaction model applied, namely n-th order reaction model. The obtained results have confirmed the complex nature of this material and the need for further modelling.
Keywords: LCW biomass; characterization; combustion; kinetics; TG analysis